1935
DOI: 10.1002/j.1537-2197.1935.tb05066.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inter‐relations of Catalase, Respiration, After‐ripening, and Germination in Some Dormant Seeds of the Polygonaceae

Abstract: Mature seeds of some species of the Polygonaceae have dormant embryos which must undergo a period of after-ripening before germination can take place. Studies reported in this paper have to do with the dormancy, after-ripening, catalase, respiration, and germination of seeds of several species of this family. Especial attention has been given the relation between the so-called enzyme catalase and the rate of respiration as found in these seeds.As the enveloping coats have a direct relation to the rate of after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1949
1949
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…This innate dormancy ensures that potentially fatal seedling emergence does not occur prior to the onset of winter. The dormancy found in fresh achenes collected in Ontario is comparable with the innate dormancy described for achenes collected and studied elsewhere (Ransom 1935;Justice 1941;Timson 1965;Porter 1966;Hammerton 1967c1, 19676). According to Timson (1965) and Hammerton (1967~1, 1967b, the degree of dormancy differs from population to population and a few strains show no innate dormancy at all.…”
Section: I1111~rte Dor-tnanysupporting
confidence: 51%
See 4 more Smart Citations
“…This innate dormancy ensures that potentially fatal seedling emergence does not occur prior to the onset of winter. The dormancy found in fresh achenes collected in Ontario is comparable with the innate dormancy described for achenes collected and studied elsewhere (Ransom 1935;Justice 1941;Timson 1965;Porter 1966;Hammerton 1967c1, 19676). According to Timson (1965) and Hammerton (1967~1, 1967b, the degree of dormancy differs from population to population and a few strains show no innate dormancy at all.…”
Section: I1111~rte Dor-tnanysupporting
confidence: 51%
“…2D). Justice (1941) and Ransom (1935) found that air drying caused a 'hard' induced dormancy in 2111 three species.…”
Section: It7d~rcecl Dottncrncymentioning
confidence: 98%
See 3 more Smart Citations